2017
DOI: 10.1523/jneurosci.2500-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Neural Entrainment to the Beat: The “Missing-Pulse” Phenomenon

Abstract: Most humans have a near-automatic inclination to tap, clap, or move to the beat of music. The capacity to extract a periodic beat from a complex musical segment is remarkable, as it requires abstraction from the temporal structure of the stimulus. It has been suggested that nonlinear interactions in neural networks result in cortical oscillations at the beat frequency, and that such entrained oscillations give rise to the percept of a beat or a pulse. Here we tested this neural resonance theory using MEG recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(167 citation statements)
references
References 53 publications
9
143
0
Order By: Relevance
“…It is possible that action might have improved timing simply by increasing the allocation of attention to the temporal stimulus features of the rhythm. However, rhythmic sequences induce strong and automatic capture of attention (Barnes & Jones, 2000;Large & Jones, 1999) as well as automatic phase-locking and error correction processes (Repp, 2005;Tal et al, 2017). We think it's therefore unlikely that action enhanced the level of attention towards temporal features more than that already induced by the rhythm itself.…”
Section: Peak Time Sdmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that action might have improved timing simply by increasing the allocation of attention to the temporal stimulus features of the rhythm. However, rhythmic sequences induce strong and automatic capture of attention (Barnes & Jones, 2000;Large & Jones, 1999) as well as automatic phase-locking and error correction processes (Repp, 2005;Tal et al, 2017). We think it's therefore unlikely that action enhanced the level of attention towards temporal features more than that already induced by the rhythm itself.…”
Section: Peak Time Sdmentioning
confidence: 97%
“…However, rhythmic sequences induce strong and automatic capture of attention (Barnes & Jones, 2000;Large & Jones, 1999) as well as automatic phase-locking and error correction processes (Repp, 2005;Tal et al, 2017). However, rhythmic sequences induce strong and automatic capture of attention (Barnes & Jones, 2000;Large & Jones, 1999) as well as automatic phase-locking and error correction processes (Repp, 2005;Tal et al, 2017).…”
Section: Peak Time Sdmentioning
confidence: 99%
“…There is increasing evidence that perception and motor entrainment to metric periodicities involve neural mechanisms that shape the representation of rhythmic inputs by selectively enhancing neural activity elicited at meter-related frequencies, regardless of the physical prominence of these frequencies in the rhythmic input (Nozaradan et al, , 2012b(Nozaradan et al, , 2016c(Nozaradan et al, , 2017cNozaradan, 2014;Chemin et al, 2014;Celma-Miralles et al, 2016;Stupacher et al, 2017;Tal et al, 2017). Recently, intracranial depth-electrode EEG recordings in humans revealed that processes from the earliest auditory cortical areas (Heschl's gyrus) shape the neural representation of rhythmic inputs in favour of increased relative amplitude of the activity corresponding to meter-related frequencies (Nozaradan et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that meter processing is related to a selective synchronization of neural activity at meter periodicities (Nozaradan et al, 2017a), the term synchronization referring here to temporal coordination or phase-locking between two signals, namely activity of large pools of neurons and periodic meter (Lenc et al, 2019). This preferential synchronization of brain activity therefore leads to selective enhancement of frequencies corresponding to the perceived meter, relative to other frequencies that are unrelated to the perceived meter but can be nonetheless prominent in the acoustic input (Nozaradan et al, , 2012Tal et al, 2017). This transformation of the rhythmic stimulus has been observed within the human auditory cortex (Nozaradan et al, 2016a, and possibly involves functional connections within an extended cortico-subcortico-cortical network supporting the processing of rhythmic input (Nozaradan et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%